Older age is associated with a reduced likelihood of ambulance transport to a trauma centre after major trauma in Perth - Brown, Elizabeth; Tohira, Hideo; Bailey, P.; Fatovich, D.; Pereira, Gavin; Finn, Judith (2019)
Objective: To describe the characteristics and outcomes of older adult (≥65 years) major trauma patients in comparison with younger adults (16–64 years). To determine whether older age is associated with a reduced likelihood of transport (directly or indirectly) to a major trauma centre and whether this is associated with in-hospital mortality. Methods: A retrospective cohort study of major trauma patients transported to hospital by St John Ambulance paramedics in Perth, Western Australia, between 1 January 2013 and 31 December 2016. Multivariate logistic regression was used to test the relationship between age and major trauma centre transport. Multivariate logistic regression analysis using inverse probability of treatment weighting was used to determine if major trauma centre transport was associated with in-hospital mortality in older adults. Results: One thousand six hundred and twenty-five patients were included; of these 576 (35%) were ≥65 years. In comparison with younger adults, older adults had more falls as their mechanism of injury (n = 358 [62%] versus n = 102 [10%], P ≤ 0.001) and more major head injuries (n = 472 [82%] versus n = 609 [58%], P ≤ 0.001). Older adults had lower odds (adjusted odds ratio 0.52, 95% confidence interval [CI] 0.35–0.78) of major trauma centre transport and this was associated with 1.7 times the likelihood of in-hospital mortality (95% CI 1.04–2.7). Conclusions: Older adults who were not transported to the trauma centre had an increased odds of in-hospital mortality. However, older age was associated with a significantly reduced likelihood of trauma centre transport. With the aging population, the development of specific prehospital triage criteria to enable the complexities of this higher-risk population to be identified is important.